Biomolecule screen identifies several inhibitors of Salmonella enterica surface colonization - Headrick, Joseph; Ohayon, Amital; Elliott, Shannon; Schultz, Jacob; Mills, Erez; Petersen, Erik (Frontiers in Bioengineering and Biotechnology, 2025)
Salmonella enterica is a foodborne pathogen commonly found in agricultural facilities whose prevalence, as well as increasing levels of disinfectant-and antibiotic-resistance, has significant costs for agriculture as well as human health. In an effort to identify potential new inhibitors of S. enterica on abiotic surfaces, we developed a biomolecule screen of nutrient-type compounds with the reasoning that nutrients would have lower toxicity in animal facilities and that bacterial nutrient utilization pathways might prove less susceptible to the development of bacterial resistance. After screening 285 nutrient-type compounds, we identified ten that significantly inhibited the ability of S. enterica to colonize a plastic surface. After conducting a dose-response curve, salicylic acid was selected for further testing due to its low minimal inhibitory concentration (62.5μM) as well as a low total inhibitory concentration (250μM). Salicylic acid was also able to inhibit surface colonization of a wide range of bacterial pathogens, suggesting our biomolecule screen might have broader application beyond S. enterica. Finally, we determined that salicylic acid was also able to inhibit S. enterica colonization of an organic surface on eggshells. Together, these results suggest that nutrienttype biomolecules may provide an avenue to combat resistant bacteria contaminating surfaces.